Online Hate Speech. Case Study of German and Polish Internet Comments in a Multimodal Perspective - Opiłowski, Roman (Hassrede – ein multidimensionales Phänomen im interdisziplinären Vergleich, 2020)
This article deals with the issue of the hate speech as a symbolic violence and at the same time as a response to real violence - the terrorist attack in Nice in July 2016. The comments on the Internet, which appeared on the social profiles of the magazines Der Spiegel and Polityka, contain negative positions and views, express contemptuous treatment, abuses and insults of the others. Such communication behaviours are conceptualized as hate speech. Using a contrasting and multimodal analysis method of the German and Polish comments, thematic fields are defined, followed by types of linguistic and multimodal activities expressing interpersonal hatred. In result, the worked-out commonalities and differences between the German and Polish online comments allow us to observe and explain interesting trends in the transnational communication space.